Futurology Education Strategy Management Perspective: A Case Study in MA Yogyakarta - Subiyantoro, Subiyantoro (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aims to analyze the futurology of education through the cultural understanding of the quality of madrasah Aliyah in Yogyakarta. This research applies qualitative research with the type of case study approach. In collecting data this study uses three techniques, namely: 1) in-depth interview; 2) participant observation, and 3) documentation study. The informants in the study were principals, teachers, educational staff, and development teams. In this study to obtain the validity of the data, Â Â triangulation was used. The results showed that the cultivation of quality culture to achieve a glorious educational future in Madrasah Aliyah was carried out by applying educational futurology from a total quality management (TQM) perspective, including continuous improvement, cultural change, reverse organization, maintaining relationships with customers, professionalism and focus on customers, as well as quality of learning.